ANALISIS PENENTUANSALURAN DISTRIBUSI YANG EFEKTIF BAGI PETANI KOPI DI DESA GONDOWIDO KECAMATAN NGEBEL KABUPATEN PONOROGO - Susantriana Dewi (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to analyze the efficiency of the marketing distribution channel for coffee products in Gondowido Village, Ngebel District, Ponorogo Regency. The type of research used is explanatory research. The sample used was 15 coffee farmers who are members of the Wonorejo Jaya Forest Farmers Group, Gondowido Village. The type of data used by researchers is primary data and secondary data. Primary data were obtained from the results of questionnaires and direct interviews conducted by researchers to 15 coffee farmers in Gondowido Village. While secondary data is data collected by researchers in the form of books, journals, articles, websites related to research topics regarding marketing, distribution and distribution channel efficiency. The data analysis technique used is a quantitative descriptive data analysis technique. The results of the data analysis show that the efficiency of the distribution channel I is 43.75% while the efficiency of the distribution channel II is 87.5%. This means that the distribution channel I is more efficient than the distribution channel II.